Evaluation of exogenous siRNA addition as a metabolic engineering tool for modifying biopharmaceuticals. (13th February 2013) - Tummala, Seshu; Titus, Michael; Wilson, Lee; Wang, Chunhua; Ciatto, Carlo; Thill, Greg; Foster, Donald; Li, Chen; Szabo, Zoltan; Guttman, Andras; Bettencourt, Brian; Jayaraman, Muthuswamy; et al.
<x xml:space="preserve">Abstract</x> Traditional metabolic engineering approaches, including homologous recombination, zinc‐finger nucleases, and short hairpin RNA, have previously been used to generate biologics with specific characteristics that improve efficacy, potency, and safety. An alternative approach is to exogenously add soluble small interfering RNA (siRNA) duplexes, formulated with a cationic lipid, directly to cells grown in shake flasks or bioreactors. This approach has the following potential advantages: no cell line development required, ability to tailor mRNA silencing by adjusting siRNA concentration, simultaneous silencing of multiple target genes, and potential temporal control of down regulation of target gene expression. In this study, we demonstrate proof of concept of the siRNA feeding approach as a metabolic engineering tool in the context of increasing monoclonal antibody (MAb) afucosylation. First, potent siRNA duplexes targeting fut8 and gmds were dosed into shake flasks with cells that express an anti‐CD20 MAb. Dose response studies demonstrated the ability to titrate the silencing effect. Furthermore, siRNA addition resulted in no deleterious effects on cell growth, final protein titer, or specific productivity. In bioreactors, antibodies produced by cells following siRNA treatment exhibited improved functional characteristics compared to antibodies from untreated cells, including increased levels of afucosylation (63%), a 17‐fold improvement in FCgRIIIa binding, and an increase in specific cell lysis by up to 30%, as determined in an Antibody‐Dependent Cellular Cytoxicity (ADCC) assay. In addition, standard purification procedures effectively cleared the exogenously added siRNA and transfection agent. Moreover, no differences were observed when other key product quality structural attributes were compared to untreated controls. These results establish that exogenous addition of siRNA represents a potentially novel metabolic engineering tool to improve biopharmaceutical function and quality that can complement existing metabolic engineering methods. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29: 415–424, 2013